Black Lives Matter, gentrification and the security state in the San Francisco Bay Area. (September 2017) - Maharawal, Manissa M
In the Fall of 2014, Black Lives Matter protests erupted across the United States and the San Francisco Bay Area became the site of nightly demonstrations that deployed a range of disruptive practices and direct actions. The content and style of these protests reflected both the national political issues raised by the Black Lives Matter movement, and highly local and regional struggles over gentrification and displacement. In this article, I analyze these protests in relation to the regional political economy of the tech-industry, the real estate booms, and the attendant 'eviction epidemic' in the region. In doing so, I lay out an analysis of the relationship between policing and gentrification in the Black Lives Matter protests in the Bay Area. In the first section, I analyze the regional political economy as the context in which these protests must be understood. In a second section, I argue that the protests created a regional protest geography that, in turn, was met by a regionalized repressive security state. Finally, I read the disruptive practices deployed by these protests as a series of complex and sophisticated contestations which embodied connections among policing, gentrification, and the regional political economy. As such, the Black Lives Matter protests produced an intersectional analysis and can be read as a regional uprising aimed to disrupt the security state.